In vitro Assessment of Antioxidant, Membrane Stabilization and Thrombolytic Activities of Ethanolic Extract of Lagenaria siceraria Fruit (Bangladesh Pharmaceutical Journal, 2024)
Lagenaria siceraria is a well-known vegetable fruit in Bangladesh. This study aimed to investigate the antioxidant, membrane stabilizing and thrombolytic activities of the ethanolic extract of L. siceraria fruits (EELSF). Total phenolic content and DPPH free radical scavenging activity tests were done to determine antioxidant properties. The anti-inflammatory effects were evaluated using heat- and hypotonic solution induced hemolysis. Human RBC from healthy volunteers were used to assess the thrombolytic activity of the extract. Ethanolic extract of L. siceraria fruits displayed noticeable antioxidant, membrane stabilizing and thrombolytic activities when compared to the standard drugs. Further studies are necessary to evaluate the pharmacological activities of different solvent fractions and plant parts of L. siceraria.Bangladesh Pharmaceutical Journal 27(1): 1-8, 2024 (January)